Modal Analysis and Test Research of Double Meshing Needle Teeth Cam Indexing Mechanism - Mingtao Liu; Fuyuan Zhang; Yanqi Li; Herong Liu; huaiyu Jin (Jixie chuandong)
In order to explore the vibration characteristics of a new type of intermittent mechanism—double meshing needle teeth cam indexing mechanism，considering the complex connection relationship between various components， the finite element model of the mechanism is established for modal analysis. The first six modal modes of the finite element model in the indexing and interval periods are extracted. Finally， the experimental modal analysis is performed on the prototype. The comparison shows that the natural frequency of the experimental modal analysis is similar to the finite element calculation. The reliability of the finite element modal analysis method is verified. According to the low order frequency of the intermission period， the structure resonance will not occur due to input. Through the modal analysis of double meshing needle teeth cam indexing mechanism， the experimental support and theoretical basis for vibration the characteristics analysis and the structural optimization design are provided.